Supramolecular synthon hierarchy in bumetanide cocrystals - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Novel cocrystals of sulfonamide drug Bumetanide with carboxamides are developed based on supramolecular synthons approach

Supramolecular synthons in bumetanide cocrystals and ternary products - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Crystal Growth & Design, 2017)
A novel design strategy for cocrystals of the diuretic sulfonamide drug bumetanide (BUM) with carboxamides is reported based on reliable supramolecular synthons. Binary cocrystals of BUM with pyridine carboxamides, pyridones, and cytosine were obtained by solvent assisted grinding followed by solution crystallization. All cocrystal structures exhibit hydrogen bonding of the coformer with the carboxylic acid group of BUM via heterosynthons which replace the acid homodimer in the drug crystal structure. Pyridones are inserted as N-H center dot center dot center dot O dimers which are in turn bonded to the acid group of BUM, while the pyridine amide coformers interact via the acid amide heterosynthon. Cocrystal polymorphs were obtained for bumetanide isonicotinamide cocrystal structure with the sulfonamide pyridine and sulfonamide acid synthons. Careful crystal packing analysis of BUM structure and nine new binary adducts gave an idea for the design ternary cocrystals, and subsequently four new ternary crystalline products were crystallized. Whereas the binary cocrystal structures were confirmed by single crystal diffraction, the ternary combinations were chatacterized by their unique powder X-ray diffraction patterns as well as by thermal and spectroscopic techniques.

Crystalline acylhydrazone photoswitches with multiple mechanical responses - Gupta, Poonam; Panda, Tamas; Allu, Suryanarayana; Borah, Silpisikha; Baishya, Anamika; Gunnam, Anilkumar; Nangia, Ashwini; Naumov, Pance; Nath, Naba K. (Crystal Growth & Design, 2019)
The advancement of our understanding of stimuli responsive molecular crystals has led to the realization that they hold great yet unexplored potential as adaptive materials. Although molecular crystals that exhibit a single mechanical response to a single input stimulus are now abundant, crystals that are capable of response to multiple stimuli are rather scarce. Here we report two photoswitchable acylhydrazone derivatives, Ac-1 and Ac-2, which respond to light as well as to mechanical force. Upon application of localized mechanical stress, the anhydrous (Ac-1a) and monohydrate (Ac-1h) crystals of Ac-1 undergo plastic shearing deformation and bending, whereas monohydrate crystals of Ac-2 undergo elastic deformation. When they are exposed to UV light, crystals of Ac-1h and Ac-2 undergo photoinduced bending; on the other hand, crystals of Ac-1a and thicker crystals of Ac-2 exhibit photosalient effect (light-induced leaping). It is demonstrated that the synergistic action of multiple stimuli (UV light and force) elicits enhanced mechanical response, and this strategy could be employed in the future to increase the efficacy of single crystal actuators.

Role of hydrogen bonding in cocrystals and coamorphous solids: indapamide as a case study - Allu, Suryanarayana; Suresh, Kuthuru; Bolla, Geetha; Mannava, M. K. Chaitanya; Nangia, Ashwini (Crystengcomm, 2019)
The stronger sulfonamide-pyridine (SO2NH2 center dot center dot center dot N-Py) and sulfonamide-carboxamide (SO2NH2 center dot center dot center dot O = C-NH) hydrogen bonds direct the formation of cocrystals, while the weaker sulfonamide-amine (SO2NH2 center dot center dot center dot N-H) hydrogen bond results in coamorphous products. IDP-PIP and IDP-ARG coamorphous solids exhibit remarkable stability under accelerated conditions.

Novel pharmaceutical cocrystals and salts of bumetanide - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
New crystalline forms of bumetanide, namely, four cocrystals, two salts, and one salt-cocrystal were crystallized. Urea and lactams such as valerolactam, caprolactam, and N-methyl caprolactam formed cocrystals with bumetanide, whereas 4-aminopyridine gave a salt. Piperazine afforded a salt hydrate, and 5-fluorocytosine gave a salt-cocrystal. The supramolecular synthons in bumetanide-lactam cocrystals are an amide dimer between drug and coformer, and acid homo dimer between bumetanide molecules. In bumetanide salts, the acid proton is transferred from bumetanide to coformer amine, whereas in bumetanide salt-cocrystal proton transfer and free acid were observed in the crystal structure. Similarly, the cytosine salt-cocrystal of bumetanide and fluorocytosine also gave a salt-cocrystal adduct. The acid proton of bumetanide is transferred to the 2-amino pyridine base of cytosine as a salt, and on the other side of the drug molecule the sulfonamide interacts with the syn amide part of cytosine. Furthermore, solubility, dissolution, and diffusion membrane permeability experiments were performed on all new solid forms. The piperazine salt shows high dissolution and permeability crossover when compared to other binary forms of bumetanide.

Salts and cocrystal of etodolac: advantage of solubility, dissolution, and permeability - Rai, Sunil K.; Allu, Suryanarayana; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
{Etodolac (ETD) is a nonsteroidal anti-inflammatory drug (NSAID) approved by the United States Food and Drug Administration (US-FDA) in 1991 for the treatment of rheumatoid arthritis. Because of its poor aqueous solubility and high permeability, ETD falls under Biopharmaceutics Classification System (BCS) Class II drug. The present study was aimed to screen stable salts and cocrystals of ETD using Generally Recognized as Safe (GRAS) and a few non-GRAS coformers. Crystallization of five salts (i.e.

The effects of cis and trans butenedioic acid on the physicochemical behavior of lumefantrine - Tomar, Devendrasingh; Lodagekar, Anurag; Gunnam, Anilkumar; Allu, Suryanarayana; Chavan, Rahul B.; Tharkar, Minakshi; Ajithkumar, T. G.; Nangia, Ashwini K.; Shastri, Nalini R. (Crystengcomm, 2022)
The present work investigates the effects of cis and trans butenedioic acid isomers (maleic acid and fumaric acid) on the crystallinity and pharmaceutical behavior of lumefantrine. Differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), attenuated total reflectance infrared spectroscopy (ATR-IR), solid-state nuclear magnetic resonance spectroscopy (ss-NMR), and single-crystal X-ray diffraction (SC-XRD) studies were employed. Lumefantrine-fumaric acid crystallized as a salt in the monoclinic space group P2(1)/c. In comparison, DSC and PXRD showed the formation of a co-amorphous solid with maleic acid. Complete proton transfer with a strong ionic interaction led to crystalline salt formation with the trans isomer, whereas weaker/fewer hydrogen bonds with the cis isomer of butenedioic acid led to a co-amorphous salt. The in vitro dissolution of both salts resulted in a similar 2.6-2.7-fold improvement in dissolution rate when compared to that of the crystalline lumefantrine. The crystalline and co-amorphous salts were stable under accelerated stability conditions (40 +/- 2 degrees C and 75 +/- 5% RH) for one month.

Synthesis of ternary cocrystals, salts, and hydrates of acefylline with enhanced dissolution and high permeability - Allu, Suryanarayana; Garai, Abhijit; Chernyshev, Vladimir V.; Nangia, Ashwini K. (Crystal Growth & Design, 2022)
Acefylline (ACF) is a stimulant xanthine derivative drug, which is formulated as a piperazine salt for the treatment of bronchial asthma. ACF falls under BCS class IV category of low solubility and poor permeability, which together limit the bioavailability and efficacy of the drug. In this work, ACF binary and ternary cocrystals, salts–cocrystals, and their polymorphs are synthesized by cocrystallization with several coformers. Two different methods were adopted for the supramolecular assembly of the ternary systems A.B.C: (1) first, binary adducts A.B or A.C were crystallized by grinding a slurry of the components in a suitable solvent and then C was added and grinding was continued; and (2) all three components were taken in a solvent slurry and ground together. The former method was found to be superior in affording the ternary salt/cocrystal. The role of laboratory seeding is implicated to explain the variation in crystallization results at different stages of the project. Crystal structures of the product’s binary and ternary systems were solved by single-crystal X-ray diffraction and powder X-ray diffraction data for structure solution. The crystal structures show the recurrence of carboxylate–pyridinium and imidazole–acid heterosynthons in the binary and ternary adducts. The intermolecular interactions between ACF and the coformer are analyzed by Hirshfeld surfaces, 2D fingerprint plots, and an energy framework. The permeability of ACF increases in binary and ternary systems with selected coformers. The fast dissolution and high permeability of ACF-PIP make this salt an improved crystalline formulation of acefylline.

Dabrafenib-panobinostat salt: improving the dissolution rate and inhibition of BRAF melanoma cells - Rai, Sunil K.; Marverti, Gaetano; Gunnam, Anilkumar; Allu, Suryanarayana; Nangia, Ashwini K. (ACS Omega, 2023)
Cocrystallization of the drug-drug salt-cocrystal of the histone deacetylase inhibitor (HDACi) panobinostat (PAN) and b-rapidly accelerated fibrosarcoma (BRAF) inhibitor dabrafenib (DBF) afforded single crystals of a two-drug salt stabilized by N+-H center dot center dot center dot O and N+-H center dot center dot center dot N- hydrogen bonds between the ionized panobinostat ammonium donor and dabrafenib sulfonamide anion acceptor in a 12-member ring motif. A faster dissolution rate for both drugs was achieved through the salt combination compared to the individual drugs in an aqueous acidic medium. The dissolution rate exhibited a peak concentration (Cmax) of approximately 310 mg cm-2 min-1 for PAN and 240 mg cm-2 min-1 for DBF at a Tmax of less than 20 min under gastric pH 1.2 (0.1 N HCl) compared to the pure drug dissolution values of 10 and 80 mg cm-2 min-1, respectively. The novel and fast-dissolving salt DBF-center dot PAN+ was analyzed in BRAFV600E melanoma cells Sk-Mel28. DBF-center dot PAN+ reduced the dose-response from micromolar to nanomolar concentrations and lowered IC50 (21.9 +/- 7.2 nM) by half compared to PAN alone (45.3 +/- 12.0 nM). The enhanced dissolution and lower survival rate of melanoma cells show the potential of novel DBF-center dot PAN+ salt in clinical evaluation.